PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING PADA PEMBELAJARAN IPS SISWA KELAS IV SD NEGERI 07 PENDOPO KABUPATEN EMPAT LAWANG - Syaiful Fajarianto; Andriana Sofiarini; Armi Yuneti (LP4MK STKIP PGRI Lubuklinggau, 2022)
The research objective was to determine student learning outcomes after applying the Contextual Teaching and Learning learning model to social studies learning significantly. This research method is in the form of an experiment with a pre-test and post-testing group research design carried out without a comparison group. The population of Grade IV students at SD Negeri 07 Pendopo, Empat Lawang Regency, consisting of 18 students, was taken using random sampling. Data collection techniques using tests in the form of essays. The data analysis technique uses a one-sample t-test. From the research, it was found that the pre-test average was 35.33 and the post-test average was 87.11 so that from the analysis using the t-test it was obtained tcount 18.89 > ttable = 1.74 so that it can be concluded that the social studies learning outcomes of students are significant. Keywords. Contextual Teaching and Learning, Learning models, Social Studies